Understanding and recommending security requirements from problem domain ontology: A cognitive three-layered approach - Kim, Bong Jae; Lee, Seok Won (Journal of Systems and Software, 2020)
Socio-technical systems (STS) are inherently complex due to the heterogeneity of its intertwined components. Therefore, ensuring STS security continues to pose significant challenges. Persistent security issues in STS are extremely critical to address as threats to security can affect entire enterprises, resulting in significant recovery costs. A profound understanding of the problems across multiple dimensions of STS is the key in addressing such security issues. However, we lack a systematic acquisition of the scattered knowledge related to design, development, and execution of STS. In this work, we methodologically analyze security issues from a requirements engineering perspective. We propose a cognitive three-layered framework integrating various modeling methodologies and knowledge sources related to security. This framework helps in understanding essential components of security and making recommendations of security requirements regarding threat analyses and risk assessments using Problem Domain Ontology (PDO) knowledge base. We also provide tool support for our framework. With the goal-oriented security reference model, we demonstrate how security requirements are recommended based on PDO, with the help of the tool. The organized acquisition of knowledge from SME groups and the domain working group provides rich context of security requirements, and also enhances the re-usability of the knowledge set.
Keywords: Knowledge sources; Layered approaches; Modeling methodology; Multiple dimensions; Reference modeling; Security issues; Security requirements; Sociotechnical systems; Ontology; Requirements engineering; Security